Job satisfaction leading to organizational excellence : a case study on expatriate academicians in Malaysian public universities - Khan, Ambareen (2017)
The purpose of this descriptive, co-relational and cross-sectional research was to gain a better understanding of the job satisfaction for the expatriate academicians working in Malaysian public sector universities which in turn leads to organizational excellence. Data were collected by the distribution of two same set of questionnaires comprising of total 73 questions which were divided in to 5 categories. One set of questionnaire was distributed among 50 expat academicians working in International Islamic University Malaysia (IIUM), in Kuala Lumpur and the other set of questionnaire was again distributed among 50 expat academicians working in Universiti Sains Malaysia (USM), located in Nibong Tebal, Penang. The results of the paper indicate that expat academicians working in Malaysian public sector universities are moderately satisfied with their jobs and committed to their organization. Employees' job satisfaction and organizational commitment were closely interrelated using intrinsic, extrinsic parameters. Strong correlation between intrinsic parameter and job satisfaction leading to organizational excellence was expected, but there was also unexpected correlation with respect to work force, work values, attitude and behaviour (WWAB) parameter. The whole research revolves around intrinsic, extrinsic and WWAB parameter so as to understand the scope of job satisfaction among the expat academicians working in Malaysian public sector universities which in turn affects organisational excellence. As job satisfaction and organizational commitment are strongly correlated, therefore it is very important to understand the parameters which impact them.